I can see (myself) clearly now: Exploring the mediating role of self-concept clarity in the association between self-compassion and indicators of well-being. - Jacob J Coutts; Rosemary L Al-Kire; Daniel J Weidler (PLoS ONE)
Is there a connection between loving oneself, knowing oneself, and mental well-being? Self-compassion-a construct that consists of self-kindness, acknowledgment of common humanity, and mindfulness-is associated with numerous positive outcomes including indicators of mental well-being. However, little research exists exploring the mechanism(s) by which self-compassion operates to influence these outcomes. It is possible that self-concept clarity, or the extent to which one's self-beliefs are clearly defined and stable, acts as such a mechanism. In the current study, we explored the mediating role of self-concept clarity in the associations between self-compassion and three indicators of mental well-being: perceived stress, depressive symptomatology, and life satisfaction. Self-compassion was significantly associated with each of the three indicators of well-being. Additionally, self-concept clarity statistically mediated the relationships between self-compassion and depressive symptomatology, perceived stress, and satisfaction with life. The results of this study suggest a potential mechanism by which self-compassion is associated with greater well-being.